Oligodendroglioma : clinical presentation, pathology, molecular biology, imaging, and treatment - Paleologos, Nina A.; Newton, Herbert B. (Academic Press is an imprint of Elsevier, 2019)
Oligodendroglioma: Clinical Presentation, Pathology, Molecular Biology, Imaging, and Treatment features the latest "cutting-edge" molecular biology, molecular therapeutics, imaging, immunotherapy, and research methods on the topic of oligodendrogliomas. The most detailed and comprehensive resource on the subject, it provides up-to-date information on clinical presentation, pathology, molecular biology, and treatment methods, including immunotherapy. This book is a critical for students, physicians and researchers in the fields of neuroscience, neuro-oncology, neurosurgery, radiation oncology, medical oncology, and others working in research or with patients